PELAKSANAAN SANKSI KEBIRI KIMIA BAGI PELAKU PEDOFILIA DALAM PERBANDINGAN HUKUM POSITIF DAN HUKUM INGGRIS - NIM. A1011211062, SAHRUL GUNAWAN (Jurnal Fatwa Hukum, 2025)
Abstract This research aims to analyze the implementation of chemical castration sanctions against pedophilia offenders through a comparative study between Indonesian positive law and English law. The study focuses on five key aspects: legal basis, type of sanction, implementation procedure, judicial decisions, and supervision mechanisms. The research employs a normative juridical method with a comparative legal approach, using literature review from both primary and secondary legal sources. The findings indicate that in Indonesia, chemical castration is regulated under Law No. 17 of 2016 on Child Protection and further elaborated through Government Regulation No. 70 of 2020 concerning the Procedures for Implementing Chemical Castration, the Installation of Electronic Detection Devices, Rehabilitation, and the Disclosure of Offenders' Identities. The implementation is mandatory based on court decisions and primarily retributive in nature, though it faces criticism related to human rights concerns and rehabilitative effectiveness. In contrast, the United Kingdom regulates sexual offences, including pedophilia, under the Sexual Offences Act 2003. The approach is medical and rehabilitative, where chemical castration is carried out voluntarily as part of a hormonal treatment program supervised by healthcare and criminal justice authorities. This method emphasizes recidivism prevention through offender rehabilitation. The study concludes that Indonesia"™s implementation of chemical castration should be re-evaluated to strike a better balance between deterrence, victim protection, and offender rehabilitation drawing lessons from the more holistic and rights-sensitive approach applied in the United Kingdom. Keyword : Chemical Castration, Pedophilia, Legal Comparison Abstrak Penelitian ini bertujuan untuk menganalisis pelaksanaan sanksi kebiri kimia terhadap pelaku pedofilia dalam perspektif perbandingan antara hukum positif Indonesia dan hukum Inggris. Fokus penelitian meliputi lima aspek utama: dasar hukum, jenis sanksi, prosedur pelaksanaan, putusan hakim, dan sistem pengawasan. Metode yang digunakan adalah yuridis normatif dengan pendekatan perbandingan hukum, melalui studi literatur terhadap sumber hukum primer dan sekunder. Hasil penelitian menunjukkan bahwa di Indonesia, sanksi kebiri kimia diatur dalam Undang- Undang Nomor 17 Tahun 2016 tentang Perlindungan Anak, serta diperinci lebih lanjut dalam Peraturan Pemerintah Nomor 70 Tahun 2020 tentang Tata Cara Pelaksanaan Tindakan Kebiri Kimia, Pemasangan Alat Pendeteksi Elektronik, Rehabilitasi, dan Pengumuman Identitas Pelaku. Pelaksanaan sanksi ini bersifat represif dan wajib dijalankan berdasarkan putusan hakim, namun pelaksanaannya menghadapi tantangan dari aspek HAM dan efektivitas rehabilitatif. Di sisi lain, Inggris mengatur penanganan terhadap pelaku kejahatan seksual, termasuk pedofilia, melalui Sexual Offences Act 2003. Pendekatannya bersifat medis dan rehabilitatif, di mana kebiri kimia dilakukan secara sukarela sebagai bagian dari program pengobatan hormonal di bawah pengawasan layanan kesehatan dan kriminal. Pendekatan ini lebih menekankan pencegahan residivisme melalui rehabilitasi. Kesimpulan penelitian ini menegaskan perlunya evaluasi terhadap pelaksanaan kebiri kimia di Indonesia agar lebih berimbang antara efek jera, perlindungan korban, dan pemulihan pelaku, seperti yang telah diterapkan di Inggris. Kata Kunci : Sanksi Kebiri Kimia, Pedofilia, Perbandingan Hukum